The Influence of Profitability, Liquidity and Asset Growth on Capital Structure with Company Size as a Moderating Variable in Food and Beverage Companies Listed on the Indonesian Stock Exchange for the 2017-2023 Period - Adelin, Dessy; Zulfitra, Zulfitra; Sahroni, Sahroni; Suharsono, Suharsono (Pascasarjana Universitas Pasundan, 2024)
This research aims to test and analyze the influence of profitability, liquidity and asset growth on capital structure with company size as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2023 period. The type of research used is associative quantitative. The research population used companies registered with food and beverage companies listed on the Indonesia Stock Exchange with observations of 133 cross section time series data. The observation period in the research used data from 2017 to 2023. The research data was then processed using Eviews 12 software. The analysis method used was panel data regression which is a combination of cross section and time series data. Panel data regression analysis is carried out through a model selection test, to determine the best model, the test results show that the Common Effect Model is the most appropriate model to use in predicting Capital Structure which is moderated by Company Size. The results of the coefficient of determination test on the model show a value of67.4398% while the remaining amount is 32.5602%can be explained by other variables not examined in this study. The research results show that Profitability has a significant negative effect on Capital Structure, Liquidity has a significant negative effect on Capital Structure, Asset Growth has a significant negative effect on Capital Structure. Company size is significantly able to moderate the relationship between Profitability and Capital Structure, Company Size is able to moderate the relationship between Liquidity and Capital Structure, Company Size is able to moderate the relationship between Asset Growth and Capital Structure. in food and beverage companies listed on the Indonesia Stock Exchange during the 2017-2023 period.